CELLULOSE ETHERS AS RHEOLOGY MODIFIERS OF REACTIVE FIRE RETARDANT PAINTS - ВАХІТОВ, РАМІЛ; КАЛАФАТ, КОСТЯНТІН; ТАРАН, НАДІЯ; БЕССАРАБОВ, ВОЛОДИМИР; РАЄНКО, ГЕННАДІЙ; ШОЛОГОН, ВІКТОР; КОРОТКІХ, МИКОЛА; ВАХІТОВА, ЛЮБОВ (Technologies and Engineering, 2024)
Purpose. To study the effect of cellulose ethers on the rheological profile of intumescent fire retardant paint with the determination of optimal structures for improving the performance properties of the paint and varnish material. Methodology. The model intumescent system was chosen as a reactive fire protection coating containing ammonium polyphosphate, melamine, pentaerythritol, titanium dioxide, and polymer. As a polymeric component, aqueous dispersions of vinyl acetate copolymers from different manufacturers were studied. Hydroxyethyl and hydroxypropyl cellulose ethers were used as cellulose thickeners, which are recognised as the most successful rheology modifiers for paints based on vinyl acetate polymers. The viscosity of the flame retardant compositions was measured using a Brookfield viscometer, and the rheological parameters were calculated using the Kesson equation. Findings. In the study, the influence of the nature of the polymer and cellulose thickener on the rheological parameters responsible for the storage and application of the paint material was investigated through the Brookfield viscosity of the fire retardant. It was found that the structure of the cellulose ester is important in regulating the viscosity of the studied intumescent compositions. The highest viscosity values are demonstrated by high molecular weight hydroxyethyl methyl cellulose (Bermocoll EM 7000 FQ). Hydroxypropyl methyl cellulose is a less effective thickener for intumescent paints of the ammonium polyphosphate/melamine/pentaerythritol composition. The nature of the polymer, in turn, has almost no effect on the viscosity of the studied compositions containing no thickener or containing Bermocoll EM 7000 FQ. Almost identical rheological profiles are observed for the studied polymer components of the intumescent compositions. The calculation of rheological parameters - viscosity at high shear rates, shear stress, yield strength using the Kesson equation - allows us to conclude that thickening of intumescent fire retardant paints with cellulose ethers is effective in preventing sedimentation during storage and has almost no effect on increasing the thickness of the paint layer that can be applied in one pass. By testing the fire protection efficiency of the coatings in a mini-oven, it was shown that the presence of cellulose ethers does not affect the fire resistance of metal plates. Originality. The influence of the cellulose thickeners structure on the rheological parameters of intumescent fire retardant paint responsible for storage and application was studied for the first time. Practical value. The obtained results make it possible to determine the optimal structures of cellulose ethers that can be used in the industrial production of intumescent paints.